Analisis Pengaruh Gaya Hidup Hedonis Terhadap Perilaku Konsumtif Dalam Perspektif Ekonomi Islam Pada Masyarakat Desa Jero Gunung Kecamatan Sakra Barat Kabupaten Lombok Timur - Sholihah, Isfi; Riswanto, Agus; Zain, Rohaeniyah; Safitri, Yuliana (Universitas Hamzanwadi, 2023)
Consumption is the most basic human need. This is clearly proven in the people of Jero Gunung Village where irrational and excessive consumption behaviour has been operating due to a hedonic lifestyle pattern. In fact, in Islamic economics, needs must be oriented towards rational and positive needs in accordance with the Islamic law. This research aims to determine the influence of a hedonic lifestyle on consumer behaviour from an Islamic economic perspective in the people of Jero Gunung Village. This type of research was quantitative correlational. The population of this research was the people of Jero Gunung Village who are indicated to have consumptive behaviour. The total research sample was 42 people using Simple Random Sampling techniques. The data analysis technique used in this research was simple regression analysis. The results of the research hypothesis test show that T count > T table with scores 3.202 > 2.021. Therefore, the hypothesis which states